Cortical compensation mechanism for swallowing recovery in patients with medullary infarction-induced dysphagia - Gu, Furong; Han, Jing; Zhang, Qiang; Li, Xiangyu; Wang, Yue; Wu, Jialing (Frontiers in Neurology, 2024)
Introduction This study aims to examine brain activity during different swallowing actions in patients with dysphagia caused by medullary infarction (MI) before and after treatment using blood oxygen level-dependent (BOLD) functional magnetic resonance imaging. Methods Fifteen patients were enrolled in this study. Brain activation during saliva swallowing and effortful saliva swallowing was observed using BOLD imaging in the acute phase of stroke and after 4 weeks of rehabilitation training. Differences in the activation of brain regions during saliva swallowing before and after treatment, during effortful saliva swallowing before and after treatment, and between the two swallowing actions before and after treatment were compared. Results In the acute phase of stroke, only the bilateral precentral and left lingual gyrus were partially activated during saliva swallowing, and there was no obvious activation in the insula. Effortful saliva swallowing activated more brain regions than saliva swallowing before treatment, including the bilateral supplementary motor area (SMA), postcentral gyrus, and right insular cortex. The number of brain regions activated during saliva swallowing increased after treatment, including the bilateral precentral gyrus, postcentral gyrus, insula, thalamus, and SMA. Discussion Cortical activation increases after recovery from dysphagia, and the increased activation of the postcentral gyrus might play a functional compensatory role. Effortful saliva swallowing is a more effective rehabilitation training method for patients with dysphagia caused by MI.